Implementation of Legal Protection for Land Rights Holders Regarding the Issuance of Duplicate Certificates: Case Study of Supreme Court Decision Number 316 K/TUN/2021: Implementasi Perlindungan Hukum bagi Pemegang Hak Atas Tanah Atas Penerbitan Sertifikat Ganda : Studi Kasus Putusan Mahkamah Agung Nomor 316 K/TUN/2021 - Lollyta Julius; Rasji Rasji (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Legal certainty in land ownership in Indonesia is mandated through the UUPA and PP 24/1997, yet its implementation remains problematic. Specific Background: One of the most severe administrative failures is the issuance of double land certificates, which undermines legal protection and public trust. Knowledge Gap: Empirical analysis remains limited regarding the ineffective implementation of agrarian regulations and the weak accountability of land officials in duplicate certificate cases. Aims: This study analyzes the implementation of legal protection for harmed land rights holders and the legal responsibility of the Land Office in Supreme Court Decision No. 316 K/TUN/2021. Results: The findings show a discrepancy between normative provisions and practice, where weak verification, manual systems, and governance failures contributed to unlawful dual certificates; sanctions imposed were minimal and not accompanied by criminal liability. Novelty: This research offers a critical, integrated assessment of normative, administrative, and judicial dimensions of duplicate certificate disputes using a focused case-law approach. Implications: Strengthening digital land registration, imposing stricter administrative and criminal sanctions, and expanding access to legal aid are essential to realizing effective agrarian legal protection and preventing recurrence. Highlights: Identifies a gap between strong agrarian norms and weak practical implementation Shows that sanctions for officials in duplicate-certificate cases remain minimal and non-deterrent. Emphasizes the need for digital registration, stricter sanctions, and better legal remedies for landowners. Keywords: Legal Protection, Land Rights, Double Land Certificates, Agrarian Law Reform